Does gastric acid suppression affect sunitinib efficacy in patients with advanced or metastatic renal cell cancer?. (June 2015) - Ha, Vincent H; Ngo, Margaret; Chu, Michael P; Ghosh, Sunita; Sawyer, Michael B; Chambers, Carole R
Introduction: Renal cell cancer is a chemotherapy-insensitive cancer treated by vascular endothelial growth factor receptor antagonists. Recently, a question has arisen on whether there is an interaction between tyrosine kinase inhibitors, such as sunitinib, and acid suppressing agents. Methods: A retrospective chart review was conducted for patients at two tertiary care centers who received sunitinib between 1 January 2006 and 31 March 2013. Using electronic systems and a province-wide electronic health records database, medication dispensing records were obtained. A univariate Cox's proportional hazard model determined if acid suppression had effects on progression-free survival and overall survival. Results: Of 383 patient charts reviewed, 231 were included in the study. Patients on intermittent acid suppression, lost to follow-up or received sunitinib for less than one week were excluded from the study. The median age of the study population was 65. Patients who received no acid suppression (n = 186) had a median progression-free survival of 23.6 weeks (95% CI, 19.0–31.9 weeks) and patients who received continuous acid suppression (n = 45) had a median progression-free survival of 18.9 weeks (95% CI, 11.0–23.7  p  = 0.04). A median overall survival of 62.4 weeks (95% CI, 42.0–82.7 weeks) was observed in the group with no acid suppression, while a median overall survival of 40.9 weeks (95% CI, 26.1–74.4 weeks) was observed in the continuous acid suppression group ( p  = 0.02). Conclusion: There was a significant difference in progression-free survival and overall survival between the acid suppressed and no acid suppression groups. Further research is required to confirm this potential interaction.